Interior of IBM Pavilion
Caption, "World's Fair, N.Y Visitors at the IBM New York World's Fair Pavilion watch a mechanical puppet show, complete with lights, music, sound effects and dialogue. Here, Sherlock Holmes exposes the evidence in the case of a stolen train to a process of two-valued logic, similar to that used in an electronic computer."